2010
DOI: 10.1523/jneurosci.4363-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Targeting Pathological Tau Prevents Cognitive Decline in a New Tangle Mouse Model

Abstract: Harnessing the immune system to clear protein aggregates is emerging as a promising approach to treat various neurodegenerative diseases. In Alzheimer's disease (AD), several clinical trials are ongoing using active and passive immunotherapy targeting the amyloid-␤ (A␤) peptide. Limited emphasis has been put into clearing tau/tangle pathology, another major hallmark of the disease. Recent findings from the first A␤ vaccination trial suggest that this approach has limited effect on tau pathology and that A␤ pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
222
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(240 citation statements)
references
References 59 publications
17
222
1
Order By: Relevance
“…Although there are potential side effects, such antibodies hold promise as treatments. However, the success of vaccination in mouse models of tauopathy (31)(32)(33)(34)(35) and synucleinopathy (43) has been puzzling in light of the fact that the target proteins are predominantly intracellular. We observed that HJ9.3, a mouse monoclonal antibody against Tau RD, inhibited the trans-cellular propagation of Tau aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are potential side effects, such antibodies hold promise as treatments. However, the success of vaccination in mouse models of tauopathy (31)(32)(33)(34)(35) and synucleinopathy (43) has been puzzling in light of the fact that the target proteins are predominantly intracellular. We observed that HJ9.3, a mouse monoclonal antibody against Tau RD, inhibited the trans-cellular propagation of Tau aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, as cognitive impairments closely correlate with the extension of tau pathology [132,133], removing neurofibrillary tangles has become one of the main therapeutic goals for the treatment of AD and FTD [134,135]. In this regard, it has been shown that both active and passive immunization against tau reduce its accumulation and slow or prevent behavioral deficits in transgenic mouse models of tauopathy [135][136][137][138][139][140][141][142].…”
Section: Immunotherapy Targeting Taumentioning
confidence: 99%
“…Similar to the amyloid immunotherapy field, tau active immunization provided the first evidence that pathologic spreading could be reduced in long-term efficacy studies [74][75][76][77]. These studies have more recently been followed by passive immunotherapy studies also showing success in reducing pathology and even rescuing motor deficits in tau transgenic mice [78,79].…”
Section: Slowing the Spreading Of Tau Pathology With Anti-tau Antibodiesmentioning
confidence: 99%